1999
DOI: 10.1111/j.1530-0277.1999.tb04068.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Benzodiazepines on Acute and Chronic Ethanol‐Induced Nociception in Rats

Abstract: These results suggest that the antinociceptive effects of both acute and chronic ethanol are at least partially mediated by GABA receptors, and that diazepam's antihyperalgesic effects may not be mediated by the GABA acid receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Accumulating evidence suggests that excessive chronic EtOH use followed by withdrawal increases pain sensitivity (Dina et al., ; Edwards et al., ; Gatch, ). As a type of subjective, negative experience, pain may affect alcohol reinforcement, and may facilitate the transition to alcohol abuse/addiction (Egli et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence suggests that excessive chronic EtOH use followed by withdrawal increases pain sensitivity (Dina et al., ; Edwards et al., ; Gatch, ). As a type of subjective, negative experience, pain may affect alcohol reinforcement, and may facilitate the transition to alcohol abuse/addiction (Egli et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperalgesia during EtOH withdrawal has been observed in various strains of rats and mice with different methods of EtOH exposure (Gatch, ). For example, Long–Evans rats on an EtOH‐containing liquid diet (6.5%) for 10 days showed hyperalgesia 3 to 12 hours after EtOH withdrawal (Gatch, ). Similarly, Wistar rats on an EtOH‐containing liquid diet for 10 days showed an increased response to the formalin test 12 hours after EtOH withdrawal (Gameiro et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that acute alcohol administration (i.p.) results in a modest lowering of the sensitivity to noxious stimuli as evaluated by tail-deflection [18], electric shocks [19], and tail-flick [20,21]. The antinociception induced by acute doses of ethanol is fully suppressed by intrathecal administration of flumazenil, a GABA A receptor antagonist [20], and increased by benzodiazepines (diazepam and midazolam) [43,44], implicating the participation of the spinal dorsal horn in the ethanol-induced analgesia.…”
Section: Where and How Ethanol Modulates Pain?mentioning
confidence: 99%
“…results in a modest lowering of the sensitivity to noxious stimuli as evaluated by tail-deflection [18], electric shocks [19], and tail-flick [20,21]. The antinociception induced by acute doses of ethanol is fully suppressed by intrathecal administration of flumazenil, a GABA A receptor antagonist [20], and increased by benzodiazepines (diazepam and midazolam) [43,44], implicating the participation of the spinal dorsal horn in the ethanol-induced analgesia. However, it has also been reported that systemic administration of non-hypnotic doses of ethanol and barbiturates to rats results in reduction of tail-flick latency and this is abolished by non-convulsant doses of the GABA A receptor channel blocker picrotoxin, indicating involvement of GABAergic mechanisms in the mediation of ethanol-induced hyperalgesia [22].…”
Section: Where and How Ethanol Modulates Pain?mentioning
confidence: 99%
See 1 more Smart Citation